ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS - Yulandari Yulandari; Asmin Asmin (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to find out the results of research analysis of students abilities through the Two Stay Two Stray (TSTS) type cooperative learning model from various literature, as well as to analyze the difficulties of students mathematical communication skills through the Two Stay Two Stray model. This type of research is descriptive qualitative and uses a literature study research method which was carried out at the Digital Library, Medan State University in July – September 2022. The instrument in this study was the author himself. The steps of this research are: (1) Designing the research. (2) Carry out the research design. (3) Analyze and provide conclusions on the results of the analysis. The analysis technique used in the selection of information related to data analysis techniques is the Miles and Huberman analysis technique. The data source used secondary data consisting of 5 journals. The conclusions of the results of this study show that: (1) The average results of tests of students mathematical communication abilities through the application of the TSTS model are: (a) The indicator of mathematical representation is 51.93%, (b) The indicator of writing/explaining mathematics was 40.31%, (c) The indicators describe is 37.94%. (2) There are several difficulties experienced by students and teachers are: (a) Students have difficulty connecting real objects, pictures, and diagrams into mathematical models, (b) Students lack confidence in communicating arguments and ideas in mathematical problems, ( c) Students are less thorough in working on questions, (d) Students have difficulty expressing mathematical ideas in the form of graphs, pictures, or tables, (e) Low student skills in understanding mathematical communication problems and drawing conclusions about mathematical communication problems, (f ) The role of the teacher is less than optimal in carrying out learning activities.